Fifteenth-century studies. - Gusick, Barbara I.; Heintzelman, Matthew Z. (Fifteenth century studies., 2012)
The fifteenth century defies consensus on fundamental issues; the period outgrew the Middle Ages and was a time of transition, a passage to modern times. 'Fifteenth-Century Studies' covers diverse aspects of the period, including liberal and fine arts, historiography, medicine, and religion. Volume 37 includes essays on René d'Anjou and authorial doubling; popular German song poetry from Oswald von Wolkenstein to Georg Forster; sacred images in Capgrave's 'Life of Saint Katherine'; milieu, John Strecche, and the Gawain-poet; Gaelic, Middle Scots, and ethnicity in three Scottish flytings; Willi.